Completeness of Science Literature Elements in Class VII Science Literacy Assessment Instruments - Falantin, Liis Kurnia; Qosyim, Ahmad (Indonesian Journal of Science Learning (IJSL), 2021)
This study was conducted with the aim of identifying the presentation of scientific literacy aspects in the scientific literacy assessment instrument for the seventh grade science material. This study uses qualitative descriptive analysis. The object of research in this study is the scientific literacy assessment instrument from the researcher Muftianah and Wahono (2018), and the researcher Arfianti (2015). The data collection technique used is literature study. The data analysis technique in this research uses content analysis. The results of the study indicate that aspects of scientific literacy have been presented well, although there is one aspect that has not been included in the scientific literacy instrument, namely the scientific process aspect. In the scientific literacy instrument for the two researchers, the aspect of scientific literacy that often appears is the aspect of science content. Thus, in measuring scientific literacy skills, all aspects of scientific literacy must be contained in scientific literacy instruments. Based on the results of the study, it can be concluded that the aspect of scientific literacy, the two instruments that have been analyzed there is one aspect that has not been included in the scientific literacy instrument, namely the scientific process aspect. In the scientific literacy instrument of the two researchers, the aspect of scientific literacy that often appears is the aspect of science content. Thus, in measuring the ability of scientific literacy, all aspects of scientific literacy must be contained in scientific literacy instruments.